Theoretical and practical features of J-scaled distortion-free HSQC - 차진욱; 박성혁 (한국자기공명학회, 2021)
Employing of 13C stable-isotopes in NMR metabolomics can give unique splitting patterns and coupling constants information originated from 13C-13C coupling interaction that provide an important structural information regarding the cellular metabolic process. But it has been known that an undesirable signal distortion in 2D heteronuclear correlation study, due to 13C-13C interaction, hampers an analysis of the coupling information. Recently, we proposed J-scaled distortion-free heteronuclear single-quantum coherence (HSQC) sequence which provides a distortion-free 13C-13C coupling information with a selective resolution enhancement of JCC splitting. In this paper, we dicuss theoretical aspect and practical feature of J-scaled HSQC pulse sequence. The conceptual explanation of orgin of the signal distortion by 13C-13C coupling interaction and design of J-scaled HSQC through exemplified results are provided in brief.